Modification of Spent Bleaching Earth with WO3 and the Application for Photocatalytic Degradation of Waste Dyestuff under Solar Light - Hindryawati, Noor; Panggabean, Aman Sentosa; Subagyono, Dirgarini Julia Nurlianti; Putri, Rinda Anisyah; Kusmiaty, Prilianda; Maniam, Gaanty Pragas (Universitas Negeri Semarang, 2019)
Degradation of blue dye waste in Sarong Samarinda production using WO3-bleaching earth (BE) has been conducted. Structural and morphological characterization has conducted using X-ray diffraction (XRD), and Scanning electron microscopy-energy dispersive spectroscopy (SEM-EDX). The X-ray diffraction results show the mineral on bleaching earth is rectorite dioctahedral mica layer and dioctahedral smectite with a ratio 2:1. The WO3 pattern is appeared after the calcination. After calcination at 500Ã‚Â°C, the WO3 is deposited homogeneously on the BE surface. The catalytic performance of WO3-BE for photodegradation of the blue dye waste under the solar light is 99.85 % within 1 h.